Manipulation of Transmembrane Transport by Synthetic K+ Ionophore Depsipeptides and Its Implications in Glucose‐Stimulated Insulin Secretion in β‐Cells. Issue 39 (24th June 2019) - García‐Calvo, José; Torroba, Tomás; Brañas‐Fresnillo, Virginia; Perdomo, Germán; Cózar‐Castellano, Irene; Li, Yu‐Hao; Legrand, Yves‐Marie; Barboiu, Mihail
Abstract: The cyclic depsipeptide cereulide toxin it is a very well‐known potassium electrogenic ionophore particularly sensitive to pancreatic beta cells. The mechanistic details of its specific activity are unknown. Here, we describe a series of synthetic substituted cereulide potassium ionophores that cause impressive selective activation of glucose‐induced insulin secretion in a constitutive manner in rat insulinoma INS1E cells. Our study demonstrates that the different electroneutral K + transport mechanism exhibited by the anionic mutant depsipeptides when compared with classical electrogenic cereulides can have an important impact of pharmacological value on glucose‐stimulated insulin secretion. Abstract : New trigger for insulin : Substitution of one hydroxy acid in the structure of an electrogenic K + ionophore, cereulide, led to a modified cyclic depsipeptide that acted as a K + ionophore with a different electroneutral transport mechanism and caused glucose‐induced insulin secretion in a constitutive manner in rat insulinoma INS1E cells (see figure).